Fluorescence Polarization Immunoassay for Express Control of Antibiotic Levels: Design and Characteristics for Chloramphenicol, as an Example - S. A. Eremin; O. Yu. Khan; V. V. Pisarev; E. A. Zvereva; A. V. Zherdev; B. B. Dzantiev (Антибиотики и Химиотерапия)
Characteristics of the fluorescence polarization immunoassay (FPIA) as a mean for express control of antibiotic levels in various specimens and its advantages vs. other analytical tests are described. The developmental stages of the analytical procedure and its parameters are considered for chlorampnenicol as an example. The analysis is based on competitive interaction of anti-chloramphenicol antibodies with the chloramphenicol-fluorophore conjugate and the potential free chloramphenicol in the specimen. The experimental results of the comparison of the chloramphenicol FPIA with the use of two conjugates differing in the length of the bridge length between the antibiotic functional groups and fluorophore (fluorescein) are presented. The requirements to the choice of the antibody and conjugate concentrations providing highly sensitive detection are characterized. The detection limit of chloramphenicol in the FPIA was 10 ng/ml and the determination of the concentrations ranged from 20 ng/ml to 10 mcg/ml. The time of the assay was 10 min.